1998
DOI: 10.1021/ma980246c
|View full text |Cite
|
Sign up to set email alerts
|

New Polymer Syntheses. 100. Multiblock Copolyesters by Combined Macrocyclic Polymerization and Silicon-Mediated Polycondensation

Abstract: Using 2,2-dibutyl-2-stanna-1,3-dioxepane (DSDOP) as cyclic initiator the macrocyclic polymerizations of ε-caprolactone were conducted in bulk at 80 °C at monomer/initiator ratios of 20/1. The resulting tin-containing supermacrocycles were reacted in situ with an excess of isophthaloyl chloride, and this reaction mixture was polycondensed with silylated Bisphenol A at temperatures between 150 and 300 °C. The characterization of the isolated copolyesters by DSC measurements and 1H NMR and 13C NMR spectroscopy pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 15 publications
0
30
0
1
Order By: Relevance
“…The same result was found when the reaction temperature was raised to 200°C at the end of the reaction time (method C-2). In this connection it should be emphasized that previous studies 7,8 (and numerous unpublished rersults) proved that polycondensations of silylated diphenols catalyzed by chloride ions do not involve transesterification up to 240°C. Therefore, the formation of 1a under the milder conditions used in this work are certainly not the result of quantitative "back-biting degradation."…”
Section: Polycondensation Of Btscmentioning
confidence: 75%
“…The same result was found when the reaction temperature was raised to 200°C at the end of the reaction time (method C-2). In this connection it should be emphasized that previous studies 7,8 (and numerous unpublished rersults) proved that polycondensations of silylated diphenols catalyzed by chloride ions do not involve transesterification up to 240°C. Therefore, the formation of 1a under the milder conditions used in this work are certainly not the result of quantitative "back-biting degradation."…”
Section: Polycondensation Of Btscmentioning
confidence: 75%
“…For most REPs of these monomers, the small Bu 2 Sn containing cycles summarized in Scheme 49 served as initiators [208][209][210][211][212][213][214][215][216][217][218][219][220][221][222][223][224][225][226] above all the seven-membered dibutyl-2-stanna-1,3-dioxepane (DSDOP). [212][213][214][215][216][217][218][219][220] The first three examples presented in Scheme 49 were known from the work of several inorganic chemists for a long time, [165][166][167][168] but those authors did not use these heterocycles as initiators. In addition to these small cycles, cyclic oligomers such as the cyclosiloxane in Scheme 49 and the cyclic and spirocyclic oligo-and polyethers presented in Schemes 39 and 50 were used as initiators.…”
Section: Reps Of Cyclic Esters By Means Of Cyclic Tin Initiatorsmentioning
confidence: 99%
“…Therefore, cyclic polymers made via REP should give nearly pure ring structures in high weight fractions. The pioneering work by Kricheldorf et al 105,129,130 in this area showed that many different cyclic lactone and lactide monomer could be polymerized using the Bu 2 Sn initiator (Scheme 5). The main drawback is that the SnAO bond within the polymer is highly susceptible to hydrolysis, degrading to its linear analogue even in air.…”
Section: Ring-expansion Polymerizationsmentioning
confidence: 99%